Letter to the editor regarding "The majority of ruptured aneurysms are small with low rupture risk scores". (January 2023) - Mehkri, Yusuf; Reilly, Thomas; Sharaf, Ramy; Shalom, Moshe
Highlights: Small aneurysms compose of the majority of ruptured intracranial aneurysms. Although small aneurysms are prone to rupture despite having low risk profiles, it should not be implied that they are more prone to rupture than large aneurysms. Further research is needed to evaluate the factors involved in intracranial aneurysm rupture risk.